Efficacy of Social Skills Training among Persons with Schizophrenia - P. Kapse, Praful (International Journal of Psychosocial Rehabilitation, 2016)
Background: Person with schizophrenia have the deterioration of personal, family, and social life. The illness leads to many disabilities in terms of interpersonal skills, communication skills, coping skills, dealing with emotions, self-care, self-control, occupational skills. Impairments in social functioning are among the most de - bilitating and treatment refractory aspects of schizophrenia (Bellack et al., 2007). Materials and Methods: The study aimed to know social skills deficits among persons with schizophrenia and to check the efficacy of the social skills training programme. A total number of 12 persons with schizophrenia, who were availing day care rehabilitation services, were selected randomly for the social skills training pro - gramme. The researcher adopted quasi experimental design without control, and interview and observer rating method used to collect data. Major Finding: Significant amount of deficits were found in self care, instrumental skills, communication skills, impulse control and social functions of the participants. The post social skills training programme there was significant improvement reported in social skills of the participants, repeated measures shows (F1.65,18.15)=93.26, p=26 significant level of change in social skills in post1 and post2 test. Conclusion: The present study reported the efficacy of social skills training in improving social skills among persons with schizophrenia who are availing day care rehabilitation facility. The model of social skills training programme were found to be effective and can be applied for larger practice in rehabilitation centres in India